Study of the Mechanical Properties of Underwater Concrete in Seawater Environments - Kurniawandy, Alex; Ismeddiyanto; Haekal, Muhammad; Zikri, Raudatul (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Anti-washout concrete (AWC) is a specialized cement-based material designed to be applied directly in underwater environments, maintain mix integrity, and prevent material washout. AWC can. This research aims to evaluate the performance of anti-washout concrete in seawater environments containing chemical compounds aggressive to concrete, by examining the ability of concrete to withstand loads, resistance to washout, and structural stability when exposed to seawater environments. The test methods used included aggregate characteristics, slump flow, compressive strength, split tensile strength, and flexural strength at 7, 14, 28, and 56 days of concrete age. The results showed that concrete with fresh water (AB) had higher compressive, split tensile, and flexural strengths than concrete using artificial seawater (AL), with a decrease in compressive strength in AL against AB of 7.29% at 14 days, 11.20% at 28 days, and 12.69% at 56 days. AWC met the minimum compressive strength requirement of 70% of the Japan Society of Civil Engineers (JSCE) standard, indicating that AWC with artificial seawater remains viable for underwater construction applications. This study's results are expected to guide the use of anti-washout concrete for various underwater applications, particularly to improve durability and reduce long-term maintenance costs for underwater infrastructure.